Odpowiedzi

2009-12-20T19:20:21+01:00
A) 3x-2b = 4a
3x=4a-2b |:3
x=1⅓a-⅔b

b)5(x-2)=2a+1
5x-10= 2a +1
5x=2a+1+10
5x= 2a +11 |:5
x=0,4a +2,2

c) 3(2x+a)=4x-3a
6x+3a= 4x - 3a | -3a
6x=4x - 6a | - 4x
2x= 6a
x= 3a

d) v=u+xt
v-u=xt
v-u/t =x

e) a(b+x)=a²c
ab+ ax = a²c
ax = a²c - ab
x = a²c - ab/a

f) a(x-b)/c=2k
ax-ab/c = 2k
ax = 2k + ab/c
x = 2k + ab/ca

g) ax/b - c = k |×b
ax - c = kb
ax = kb +c
x + kb +c/a

h) x/c + a/b = t |×c
x + a/b = tc
x = tc - a/b

i) x-a/b = 3c-x/k
x = 3c-x/k + a/b |×k
xk = 3c-x + a/b
x = 3c-x + a/b - k

9 1 9
  • Użytkownik Zadane
2009-12-20T19:19:28+01:00
A)3x-2b=4a
3x=4a+2b /:3
x=4/3a(cztery trzecie a)+2/3b
b) 5(x-2)=2a+1
5x-10=2a+1
5x=2a+1+10
5x=2a+11 /:5
x=2/5a+11/:5
c)3(2x+a)=4x-3a
6x+3a=4x-3a
6x-4x=-3a-3a
2x=-6a /:2
x=-3a
d)v=u+xt
-xt=u-v /t
-x=u/t-v/t /:(-1)
x=u/t-v/t
e)a(b+x)= a <kwadrat> c
ab+ax=a<kwadrat>c
ax=a<kwadrat>c-ab /:a
x=(a<kwadrat>c-ab)/2